Avaliação da biodigestãodo resíduo de maracujá in natura e pré-tratado com hidróxido de sódio e ensilagem, inoculados com excretas de aves. - Melo, Marcelo José de (2016)
In order to reduce dependence on fossil and non-renewable fuels, we have sought alternative sources that are environmentally correct to meet this demand. Biomass has been used as an energy source, not only as a means to reduce global environmental impacts, but also to contribute to the energy matrix. The aim of this research was to evaluate the anaerobic digestion and biogas production generated from the shells and passion fruit seeds in a consortium with bird excreta as inoculum using nine reactors, segregated into three types of treatment. The first treatment using only casaca and seeds of passion fruit in natura, the second compound with passion fruit peel and (NaOH) and the third using the passion fruit peel pre-treated through silage. In all treatments, bird excreta were fed with passion fruit seeds as inoculum. The procedure was observed during 60 days and generated a 45 day gas reading. The reactor that obtained the best performance was the one with passion fruit residue treated with NaOH, having as peak of production of methane (CH4) the 26th day, and the value of 0.0063 mmol.dia-1 of accumulated CH4.